Existing Knowledge on Breast Cancer among Secondary School Students of Biratnagar - Basnet, Saraswati; Silwal, Suvekshya; Khadgi, Deepika; Mahato, Anju Kumari; Mehata, Yogendra Prasad; Chaudhary, Angira Kumari (Journal of Biratnagar Nursing Campus, 2025)
Background:  Breast cancer is leading cause of mortality among women and most frequently diagnosed cancer globally, and its burden has increased in recent decades. The objective of this study is to assess the knowledge on breast cancer among secondary level schools’ students.Methods: A cross-sectional analytic design was used to conduct the study. The duration the study was six months from, form December 2022 to June 2023. The settings of the study were four secondary schools of Biratnagar Metropolitan. Four hundred twelve (412) students of selected secondary schools were included as the study population. A semi- structured questionnaire was used for data collection. Descriptive and inferential statistics were used for data analysis.Results: The finding revealed that most (93.2%) of students were aged 14- 18 years. One fourth of the respondents had good knowledge (25.7%), while more than two-thirds of them (74.3%) had poor knowledge. There are statistically significant associations between the level of breast cancer knowledge and socio-demographic factors, including age, place of residence, and family history of cancer.Conclusion: The study concluded that only one-fourth of the students had a good level of knowledge. Therefore, an awareness program may enhance the knowledge of the study of other class of concerned school.